Strategi Kepala Madrasah Dalam Menentukan Kebijakan Pembelajaran Era Covid 19 Studi Kasus Kepala Madrasah Ibtidaiyah NW Pondok Gedang - Muhammad Sufyan Ats-Tsauri; Erni Munastiwi (Elementeris : Jurnal Ilmiah Pendidikan Dasar Islam, 2020)
Government policies that make lockdown systems in every school and university. Learning System Policy to antispaced the transmission of Covid-19. The type of research used is qualitative, i.e. field research, object research as data source is head of Madrasah Ibtidaiyah NW Ponodok Gedang. The head of the Madrasah policy is quick to pay attention to the policy presented by the Ministry of Central Education, 4 students have the education in this regard as principal policy reference: first learning (online), interactively, both learning to students about proficiency in the value of life, which is learning to suit the environment conditions of each home, especially the understanding of the virus Mers Garry 19, all three online learning implementation in the concept House should be adjusted to the situation and condition of each student. It is not targeted to all students, who should be aware of the environmental conditions of each student, including access to the Internet network in each of the fourth child areas for teachers. The task given to students is not assessed as the judgment is usually in the School. The condition of students lacking knowledge of online learning UGA as a reason to establish the policy of the implementation of the learning process so that the policy taken by the head of Madrasah Ibtidaiyah is to look at the teacher's captain in the online media to master the Learning era pandemic Garry 19 continue to be performed at home with the BDR system (learning from home)